(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2023)
Infertility (Stree Vandhyatva) is defined as not being able to get pregnant despite having frequent, unprotected coitus for at least a year for most couples. Among the three eshanas that are described in our context, Putraishana-aspiration for the child is the strongest desire of all the married couple. Beeja especially streebeeja is the only entity which don’t have any alternative as it is the principle component which resembles a family in future as their own being. The beejdushti is related with anovulation. Ovarian factor contribute 15-25% and is the second common cause of infertility. As compared to modern science, this beejdushti can be well treated with Nasya karma explained in Ayurveda. Nasya means nothing but administration of medicine through nose. Hypothalamus plays an important role in infertility due to anovulation. Nasya acts on hypothalamus as well as pituitary gland.